Peran Penuntut Umum pada Pendekatan Restorative Justice Kasus Tindak Pidana Penganiayaan (LEGAL DIALOGICA, 2025)
This study aims to identify the pros and cons of implementing a restorative justice strategy in abuse cases handled by the Wajo District Attorney's Office, as well as the role of public prosecutors in this approach in Wajo Regency. This research is an empirical legal study. Interviews using a pre-designed questionnaire were used as a means of collecting data and information. The results of the study indicate that public prosecutors not only carry out their prosecutorial function but also act as facilitators in resolving cases through deliberation between the perpetrator and the victim. The success of this approach is supported by the victim's willingness to forgive, the involvement of community and religious leaders, and the restitution of losses by the perpetrator. However, there are obstacles such as the victim's refusal to reconcile, unrealistic compensation demands, limited time by the authorities, low public understanding, and the potential for mediation failure. The recommendations in this study for the Wajo District Attorney's Office include continuing to strengthen the restorative justice implementation mechanism by providing special training for prosecutors on penal mediation techniques and empathetic communication so that the peace process can run more effectively. It is also necessary to increase understanding of the concept of restorative justice through socialization or legal counseling to avoid misunderstandings or resistance to the out-of-court settlement process.Abstrak:Penelitian ini bertujuan untuk mengidentifikasi pro dan kontra penerapan strategi keadilan restoratif dalam kasus penganiayaan yang ditangani oleh Kejaksaan Negeri Wajo, serta peran jaksa penuntut umum dalam pendekatan di Kabupaten Wajo. Penelitian ini merupakan studi hukum empiris. Wawancara menggunakan kuesioner yang telah disusun sebelumnya digunakan sebagai sarana pengumpulan data dan informasi. Hasil penelitian menunjukkan bahwa penuntut umum tidak hanya menjalankan fungsi penuntutan, tetapi juga berperan sebagai fasilitator dalam penyelesaian perkara melalui musyawarah antara pelaku dan korban. Keberhasilan pendekatan ini didukung oleh kesediaan korban memaafkan, keterlibatan tokoh masyarakat dan agama, serta pengembalian kerugian oleh pelaku. Namun, terdapat hambatan seperti penolakan korban untuk berdamai, tuntutan ganti rugi yang tidak realistis, keterbatasan waktu aparat, rendahnya pemahaman masyarakat, dan potensi kegagalan mediasi. Rekomendasi dalam penelitian ini bagi Kejaksaan Negeri Wajo, disarankan untuk terus memperkuat mekanisme pelaksanaan restorative justice dengan memberikan pelatihan khusus bagi jaksa mengenai teknik mediasi penal dan komunikasi empatik agar proses perdamaian dapat berjalan lebih efektif serta diperlukan peningkatan pemahaman tentang konsep restorative justice melalui sosialisasi atau penyuluhan hukum agar tidak terjadi kesalahpahaman atau resistensi terhadap proses penyelesaian di luar pengadilan.Kata Kunci: Penuntut Umum, Tindak Pidana Penganiayaan, Keadilan Restoratif.